X-Git-Url: http://lambda.jimpryor.net/git/gitweb.cgi?p=lambda.git;a=blobdiff_plain;f=advanced_topics%2Fmonads_in_category_theory.mdwn;h=d5c0941da9a74e539a9e4944ca686ed0473ae91e;hp=588d1a30f237dcad0f82b0a26d875af84b9459da;hb=115b2bc2456adb01295e074ccc825942e45c46c0;hpb=c0a6070f7c11da38419b5e5da90afeddc6520b95 diff --git a/advanced_topics/monads_in_category_theory.mdwn b/advanced_topics/monads_in_category_theory.mdwn index 588d1a30..d5c0941d 100644 --- a/advanced_topics/monads_in_category_theory.mdwn +++ b/advanced_topics/monads_in_category_theory.mdwn @@ -393,120 +393,209 @@ Finally, we substitute ((join G') -v- (M γ) -v- φ) for - (ρ <=< γ) is a transformation from G to MR', so - (ρ <=< γ) <=< φ becomes: ((join R') (M (ρ <=< γ)) φ) + (ρ <=< γ) is a transformation from G to MR', so + (ρ <=< γ) <=< φ becomes: ((join R') (M (ρ <=< γ)) φ) which is: ((join R') (M ((join R') (M ρ) γ)) φ) - similarly, ρ <=< (γ <=< φ) is: + similarly, ρ <=< (γ <=< φ) is: ((join R') (M ρ) ((join G') (M γ) φ)) - substituting these into (ii), and helping ourselves to associativity on the rhs, we get: - ((join R') (M ((join R') (M ρ) γ)) φ) = ((join R') (M ρ) (join G') (M γ) φ) + substituting these into (ii), and helping ourselves to associativity on the rhs, we get: + ((join R') (M ((join R') (M ρ) γ)) φ) = ((join R') (M ρ) (join G') (M γ) φ) - which by the distributivity of functors over composition, and helping ourselves to associativity on the lhs, yields: - ((join R') (M join R') (MM ρ) (M γ) φ) = ((join R') (M ρ) (join G') (M γ) φ) + which by the distributivity of functors over composition, and helping ourselves to associativity on the lhs, yields: + ((join R') (M join R') (MM ρ) (M γ) φ) = ((join R') (M ρ) (join G') (M γ) φ) - which by lemma 1, with ρ a transformation from G' to MR', yields: - ((join R') (M join R') (MM ρ) (M γ) φ) = ((join R') (join MR') (MM ρ) (M γ) φ) + which by lemma 1, with ρ a transformation from G' to MR', yields: + ((join R') (M join R') (MM ρ) (M γ) φ) = ((join R') (join MR') (MM ρ) (M γ) φ) - which will be true for all ρ,γ,φ only when: - ((join R') (M join R')) = ((join R') (join MR')), for any R'. + which will be true for all ρ,γ,φ only when: + ((join R') (M join R')) = ((join R') (join MR')), for any R'. - which will in turn be true when: - (ii') (join (M join)) = (join (join M)) + which will in turn be true when: + (ii') (join (M join)) = (join (join M)) (iii.1) (unit G') <=< γ = γ when γ is a natural transformation from some FG' to MG' - (iii.1) (unit F') <=< φ = φ ==> - (unit F') is a transformation from F' to MF', so: - (unit F') <=< φ becomes: (join F') (M unit F') φ - which is: (join F') (M unit F') φ - substituting in (iii.1), we get: - ((join F') (M unit F') φ) = φ + (unit G') is a transformation from G' to MG', so: + (unit G') <=< γ becomes: ((join G') (M unit G') γ) - which will be true for all φ just in case: + substituting in (iii.1), we get: + ((join G') (M unit G') γ) = γ - ((join F') (M unit F')) = the identity transformation, for any F' - - which will in turn be true just in case: + which will be true for all γ just in case: + ((join G') (M unit G')) = the identity transformation, for any G' + which will in turn be true just in case: (iii.1') (join (M unit) = the identity transformation - (iii.2) γ = γ <=< (unit G) + (iii.2) γ = γ <=< (unit G) when γ is a natural transformation from G to some MR'G - (iii.2) φ = φ <=< (unit F) ==> - φ is a transformation from F to MF', so: - unit <=< φ becomes: (join F') (M φ) unit - substituting in (iii.2), we get: - φ = ((join F') (M φ) (unit F)) - -------------- - which by lemma (2), yields: - ------------ - φ = ((join F') ((unit MF') φ) + unit <=< γ becomes: ((join R'G) (M γ) unit) + + substituting in (iii.2), we get: + γ = ((join R'G) (M γ) (unit G)) + + which by lemma 2, yields: + γ = ((join R'G) ((unit MR'G) γ) + + which will be true for all γ just in case: + ((join R'G) (unit MR'G)) = the identity transformation, for any R'G + + which will in turn be true just in case: + (iii.2') (join (unit M)) = the identity transformation + - which will be true for all φ just in case: - ((join F') (unit MF')) = the identity transformation, for any F' +Collecting the results, our monad laws turn out in this format to be: - which will in turn be true just in case: +
+	For all ρ, γ, φ in T,
+	where φ is a transformation from F to MF',
+	γ is a transformation from G to MG',
+	ρ is a transformation from R to MR',
+	and F'=G and G'=R:
+
+	    (i') ((join G') (M γ) φ) etc also in T
+
+	   (ii') (join (M join)) = (join (join M))
+
+	(iii.1') (join (M unit)) = the identity transformation
 
 	(iii.2') (join (unit M)) = the identity transformation
 
-Collecting the results, our monad laws turn out in this format to be: +Getting to the functional programming presentation of the monad laws +-------------------------------------------------------------------- +In functional programming, `unit` is sometimes called `return` and the monad laws are usually stated in terms of `unit`/`return` and an operation called `bind` which is interdefinable with `<=<` or with `join`. + +The base category C will have types as elements, and monadic functions as its morphisms. The source and target of a morphism will be the types of its argument and its result. (As always, there can be multiple distinct morphisms from the same source to the same target.) + +A monad `M` will consist of a mapping from types `'t` to types `M('t)`, and a mapping from functions f:C1→C2 to functions M(f):M(C1)→M(C2). This is also known as liftM f for `M`, and is pronounced "function f lifted into the monad M." For example, where `M` is the list monad, `M` maps every type `'t` into the type `'t list`, and maps every function f:x→y into the function that maps `[x1,x2...]` to `[y1,y2,...]`. + + +In functional programming, instead of working with natural transformations we work with "monadic values" and polymorphic functions "into the monad" in question. + +A "monadic value" is any member of a type M('t), for any type 't. For example, a list is a monadic value for the list monad. We can think of these monadic values as the result of applying some function (φ : F('t) → M(F'('t))) to an argument `a` of type `F('t)`. + + +Let `'t` be a type variable, and `F` and `F'` be functors, and let `phi` be a polymorphic function that takes arguments of type `F('t)` and yields results of type `MF'('t)` in the monad `M`. An example with `M` being the list monad: + +
+	let phi = fun ((_:char, x y) -> [(1,x,y),(2,x,y)]
 
- when φ a transformation from F to MF', γ a transformation from F' to MG', ρ a transformation from G' to MR' all in T: - (i') ((join G') (M γ) φ) etc also in T +Here phi is defined when `'t = 't1*'t2`, `F('t1*'t2) = char * 't1 * 't2`, and `F'('t1 * 't2) = int * 't1 * 't2`. - (ii') (join (M join)) = (join (join M)) - (iii.1') (join (M unit)) = the identity transformation +Now where `gamma` is another function into monad `M` of type F'('t) → MG'('t), we define: - (iii.2')(join (unit M)) = the identity transformation +
+	gamma =<< phi a  =def. ((join G') -v- (M gamma)) (phi a)
+
+	                 = ((join G') -v- (M gamma) -v- phi) a
+					 = (gamma <=< phi) a
 
+Hence: +
+	gamma <=< phi = fun a -> (gamma =<< phi a)
+
-Getting to the functional programming presentation of the monad laws --------------------------------------------------------------------- -In functional programming, unit is usually called "return" and the monad laws are usually stated in terms of return and an operation called "bind" which is interdefinable with <=< or with join. +`gamma =<< phi a` is called the operation of "binding" the function gamma to the monadic value `phi a`, and is usually written as `phi a >>= gamma`. -Additionally, whereas in category-theory one works "monomorphically", in functional programming one usually works with "polymorphic" functions. +With these definitions, our monadic laws become: -The base category C will have types as elements, and monadic functions as its morphisms. The source and target of a morphism will be the types of its argument and its result. (As always, there can be multiple distinct morphisms from the same source to the same target.) -A monad M will consist of a mapping from types C1 to types M(C1), and a mapping from functions f:C1→C2 to functions M(f):M(C1)→M(C2). This is also known as "fmap f" or "liftM f" for M, and is called "function f lifted into the monad M." For example, where M is the list monad, M maps every type X into the type "list of Xs", and maps every function f:x→y into the function that maps [x1,x2...] to [y1,y2,...]. +
+	Where phi is a polymorphic function from type F('t) -> M F'('t)
+	and gamma is a polymorphic function from type G('t) -> M G' ('t)
+	and rho is a polymorphic function from type R('t) -> M R' ('t)
+	and F' = G and G' = R, 
+	and a ranges over values of type F('t) for some type 't,
+	and b ranges over values of type G('t):
+
+	      (i) γ <=< φ is defined,
+			  and is a natural transformation from F to MG'
+	==>
+		(i'') fun a -> gamma =<< phi a is defined,
+			  and is a function from type F('t) -> M G' ('t)
 
 
 
+	     (ii) (ρ <=< γ) <=< φ  =  ρ <=< (γ <=< φ)
+	==>
+			  (fun a -> (rho <=< gamma) =<< phi a)  =  (fun a -> rho =<< (gamma <=< phi) a)
+			  (fun a -> (fun b -> rho =<< gamma b) =<< phi a)  =  (fun a -> rho =<< (gamma =<< phi a))
 
-A natural transformation t assigns to each type C1 in C a morphism t[C1]: C1→M(C1) such that, for every f:C1→C2:
-	t[C2] ∘ f = M(f) ∘ t[C1]
+	   (ii'') (fun b -> rho =<< gamma b) =<< phi a  =  rho =<< (gamma =<< phi a)
 
-The composite morphisms said here to be identical are morphisms from the type C1 to the type M(C2).
 
 
+	  (iii.1) (unit G') <=< γ  =  γ
+	          when γ is a natural transformation from some FG' to MG'
 
-In functional programming, instead of working with natural transformations we work with "monadic values" and polymorphic functions "into the monad" in question.
+			  (unit G') <=< gamma  =  gamma
+			  when gamma is a function of type FQ'('t) -> M G'('t)
+
+			  fun b -> (unit G') =<< gamma b  =  gamma
+
+			  (unit G') =<< gamma b  =  gamma b
+
+			  As below, return will map arguments c of type G'('t)
+			  to the monadic value (unit G') b, of type M G'('t).
+
+	(iii.1'') return =<< gamma b  =  gamma b
+
+
+
+	  (iii.2) γ  =  γ <=< (unit G)
+	          when γ is a natural transformation from G to some MR'G
+	==>
+			  gamma  =  gamma <=< (unit G)
+			  when gamma is a function of type G('t) -> M R' G('t)
+
+			  gamma  =  fun b -> gamma =<< ((unit G) b)
+
+			  Let return be a polymorphic function mapping arguments
+			  of any type 't to M('t). In particular, it maps arguments
+			  b of type G('t) to the monadic value (unit G) b, of
+			  type M G('t).
+
+			  gamma  =  fun b -> gamma =<< return b
+
+	(iii.2'') gamma b  =  gamma =<< return b
+
+ +Summarizing (ii''), (iii.1''), (iii.2''), these are the monadic laws as usually stated in the functional programming literature: + +* `fun b -> rho =<< gamma b) =<< phi a = rho =<< (gamma =<< phi a)` + + Usually written reversed, and with a monadic variable `u` standing in + for `phi a`: + + `u >>= (fun b -> gamma b >>= rho) = (u >>= gamma) >>= rho` -For an example of the latter, let φ be a function that takes arguments of some (schematic, polymorphic) type C1 and yields results of some (schematic, polymorphic) type M(C2). An example with M being the list monad, and C2 being the tuple type schema int * C1: +* `return =<< gamma b = gamma b` - let φ = fun c → [(1,c), (2,c)] + Usually written reversed, and with `u` standing in for `phi a`: -φ is polymorphic: when you apply it to the int 0 you get a result of type "list of int * int": [(1,0), (2,0)]. When you apply it to the char 'e' you get a result of type "list of int * char": [(1,'e'), (2,'e')]. + `u >>= return = u` -However, to keep things simple, we'll work instead with functions whose type is settled. So instead of the polymorphic φ, we'll work with (φ : C1 → M(int * C1)). This only accepts arguments of type C1. For generality, I'll talk of functions with the type (φ : C1 → M(C1')), where we assume that C1' is a function of C1. +* `gamma b = gamma =<< return b` -A "monadic value" is any member of a type M(C1), for any type C1. For example, a list is a monadic value for the list monad. We can think of these monadic values as the result of applying some function (φ : C1 → M(C1')) to an argument of type C1. + Usually written reversed: + `return b >>= gamma = gamma b` +